EVALUATION OF PANCASILA EDUCATION AMONG HEALTH STUDENT DURING COVID-19 PANDEMIC IN GRESIK CITY - Nourma Yunita; Sri Suryanti (JURNAL PENDIDIKAN KEWARGANEGARAAN, 2022)
This study aims to evaluate the knowledge of health students in Pancasila education with online teaching methods, namely zoom meeting and SPADA (Online Learning System). Health students are prospective health workers who will later be involved in the health profession. With humanitarian responsibilities that will be borne in the future, health students need to have cognitive abilities in the field of citizenship so that they can perform their professional performance in accordance with the integrity and applicable rules. The method used is semi-experimental by conducting two different learning methods on 116 health students at the University of Muhammadiyah Gresik. This research was conducted in januari - februari 2022. The results of this study indicate that the knowledge of health students related to pancasila education is in the good category. In addition, the results of this study indicate that there is no difference in Pancasila knowledge between health students using the Zoom Meeting and SPADA online learning methods.